The effect of mycorrhizal inoculation on forage and non-forage plant growth and nutrient uptake under field conditions - Ortas I. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
The effect of mycorrhizal inoculation on nitrogen fixing and non-fixing plant growth and macro- and micro-nutrient uptake were observed under field conditions. Several field experiments were set up on the research farm of Çukurova University (Eastern Mediterranean region). In one experiment clover, lentil, onion, garlic, chickpea and horse-bean plants were used. Cocktail mycorrhiza was used as a mycorrhizal strain. The results have shown, that in mycorrhizal plots, the yields of onion, garlic, chickpea, clover, lentil and horse-bean plants were higher than in non-mycorrhizal plants. Mycorrhizal inoculation also increased Cu and Zn content in the shoot. In another experiment carried out under field conditions for three successful years on horse-bean, chickpea and soybean plants, mycorrhizal inoculation was successfully applied in sterile and non-sterile soil conditions with and without phosphorous application. After a three-year evaluation it was found that under field conditions mycorrhizal inoculation significantly increased horse-bean, chickpea and soybean. Likewise, applying more P resulted in increased yield. Garlic, chickpea and horse-bean did not grow very well in fumigated plots compared to the non-fumigated ones. It was found that in fumigated plots mycorrhizal inoculation significantly increased growth of horse-bean and garlic. Mycorrhizal inoculation also increased nutrient uptake of both plants. Inoculation of the soil with mycorrhizae strains significantly increased plant growth and P uptake of plants, especially under low P supply. In low P application, plant roots were strongly infected and consequently increased plant growth, but with high P level applications there was a slight reduction in root infection. The results show that mycorrhizal inoculation is an effective practice for improving crop production in P-deficient soils.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)